Common Accidents: How I Came to Write "My Father Glows in the Dark." - Couto, Nancy Vieira (Salamander)
Presents the author's account on how she came to write "My Father Glows in the Dark." Description of her usage of a DOS computer; Significance of accidents while trying to create poetry.